Waiting for Geotropic Forces: Bergsonian Duration and the Ecological Sympathies of Biodesign. (June 2022) - Williams, Nina
Biodesign disrupts the traditional temporalities of expectation and demand in wider design economies because designers are not selecting from a range of prefabricated samples from which they manufacture a product. Instead, they are plunged into the durations of other organisms for the simple reason that they must wait for something to grow. Situated in this context, this article considers how we might conceptualize these events of "waiting" such that we intensify their importance for ecological thought. In the philosophy of Henri Bergson, events of waiting are important as a mode of intuiting a register of movement beyond human habits of perception, what he refers to as duration . In this article, I suggest that thinking events of waiting in biodesign via Bergson intervenes in debates surrounding posthuman creativity, not because it multiplies creative agents but because it cultivates a sympathy for temporal ecologies from which human perception is alienated.